Effect of concentration sulfuric acid on alumina extraction from napa soil - Fiqrhatul Ilmi; Mawardi Mawardi (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2023)
West Sumatra is one of Indonesia's provinces with abundant and diverse natural potential. Based on data from the Department of Energy and Mineral Resources, West Sumatra province has a rich potential for metal and non-metallic minerals. Some types of minerals include gold lead (Au), zinc (Zn), manganese (Mn), coal, ironstone, and others. In iron ore, metal minerals contained iron minerals and gangue minerals such as silica and alumina. Napa soil is one of the materials found in West Sumatra containing aluminosilicate with a SiO2/ Al2O3 ratio of 63.20 %/ 16.55 %. It also contains TiO2, CaO, and K2O. Extraction of alumina generally using HCl or H2SO4 solvent. In previous research, HCl has been used as a solvent in extracting alumina from napa soil. Based on the literature search, no one has used H2SO4 as a solvent in the extraction of alumina from napa soil; therefore, it is necessary to conduct research as a material for further study. Therefore, this study will be conducted on variations in the concentration of acid solvents to determine the optimum amount of alumina products in the extraction of alumina in napa soil. In this study, the optimum results obtained alumina extraction with variations in the sulfuric acid concentration at a concentration of 6.0 M, with a % yield of 26.73%. The XRF analysis of alumina extraction showed that the Al2O3 content increased by 72.89%. Characterization of Alumina by FTIR indicated the presence of Al-O, Al-OH.